Incidents of snake fungal disease caused by the fungal pathogen Ophidiomyces ophidiicola in Texas - Lizarraga, Alan J.; Hart, Lezley; Wright, R. Michele; Williams, Lance R.; Glavy, Joseph S. (Frontiers in Fungal Biology, 2023)
The pathogen Ophidiomyces ophidiicola, widely known as the primary cause of snake fungal disease (SFD) has been detected in Texas’s naïve snakes. Our team set out to characterize O. ophidiicola’s spread in eastern Texas. From December 2018 until November 2021, we sampled and screened with ultraviolet (UV) light, 176 snakes across eastern Texas and detected 27. O. ophidiicola’s positive snakes using qPCR and one snake in which SFD was confirmed via additional histological examination. Upon finding the ribbon snake with clear clinical display, we isolated and cultured what we believe to be the first culture from Texas. This cultured O. ophidiicola TX displays a ring halo formation when grown on a solid medium as well as cellular autofluorescence as expected. Imaging reveals individual cells within the septated hyphae branches contain a distinct nucleus separation from neighboring cells. Overall, we have found over 1/10 snakes that may be infected in East Texas, gives credence to the onset of SFD in Texas. These results add to the progress of the disease across the continental United States.